Penerapan Teknologi RFID untuk Monitoring Presensi dan Saldo Deposit Santri - Nur Faizah, Nur Fadila; Mustofa, Ahmad; Jauhari, Moh. (Politeknik Negeri Madura, 2024)
Attendance is a method used to monitor someone's attendance at an activity. Attendance data collection is currently using the manual, namely by signing on the list of names that have been provided. The weakness of this manual system is that the timeliness in attendance is less accurate. In addition, at Islamic boarding schools, students are prohibited from holding personal money or remittances from their respective parents. This is done to avoid bad events such as losing money, overspending, and others. Based on these problems, this final project will create an attendance system and an RFID-based payment instrument equipped with reports in the form of notifications to WhatsApp. The purpose of this system is to provide convenience in managing attendance data. This system uses an RFID reader input as an RFID card reader, nodeMCU ESP8266 as a microcontroller, and output in the form of an LCD and buzzer as indicators, as well as reports in the form of notifications to WhatsApp. The output of this final project the system can detect and distinguish between registered and unregistered RFID to make attendance and payments. The system can also send notifications on WhatsApp every time you make attendance and payments with an average duration of 6 seconds.